Exploring the Role of Situational Cues in Apparel Consumers' Impulsive Buying Behaviour - Vishal Trivedi; Pradeep Joshi (Tekstilec, 2024)
This study evaluates the role of situational cues (time availability, money availability, salesperson’s behaviour, promotional offers and payment methods) on the impulse purchasing conduct of apparel buyers in brick-and-mortar stores. The study sheds light on the key determinants of impulse purchases in offline apparel shopping by delving into the dynamic interaction between situational cues (factors) and consumer impulse-buying decisions. A survey questionnaire was used, based on previous literature, to collect primary data from 325 respondents from Delhi (NCR), India in the sample. The data were examined using regression analysis, correlation analysis and factor analysis. According to the findings of the study, impulsive apparel shopping behaviour is significantly influenced by situational cues such as time availability, money availability, salesperson behaviour, promotional offers and payment methods. In addition, the findings indicate that salespeople’s behaviour, promotional offers and payment methods are closely linked to apparel consumers' impulse buying behaviour. This study offers some recommendations for retailers to enhance their retail strategies to increase consumers' impulsive purchases of apparel.